2021
DOI: 10.1002/ijgo.13818
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adenomyosis on the prognosis of patients with endometrial cancer

Abstract: Ϯ Diego Raimondo and Antonio Raffone equally contributed to the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Type I endometrial cancers are commonly associated with a relatively good prognosis [8]. A recent meta-analysis showed that women with adenomyosis and endometrial cancer had longer overall survival when compared to women with endometrial cancer without adenomyosis [21]. However, in this study it was not possible to calculate multivariate hazard ratios.…”
Section: Endometrial Cancer Subtypesmentioning
confidence: 79%
“…Type I endometrial cancers are commonly associated with a relatively good prognosis [8]. A recent meta-analysis showed that women with adenomyosis and endometrial cancer had longer overall survival when compared to women with endometrial cancer without adenomyosis [21]. However, in this study it was not possible to calculate multivariate hazard ratios.…”
Section: Endometrial Cancer Subtypesmentioning
confidence: 79%
“…Although the association between adenomyosis and EC prevalence has not been proven [9], several authors have hypothesized a better EC prognosis in patients with underlying uterine adenomyosis [10][11][12]. However, the underlying factors are still unknown.…”
Section: Main Findings and Interpretationmentioning
confidence: 99%
“…The presence of co-existent adenomyosis has been reported to halve the risk of death in EC patients [10][11][12]. Unfortunately, it is still unclear if this better prognosis is related to a more favorable clinical profile (e.g., younger age or lower BMI) or a different underlying pathogenesis of EC in this subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a multivariate analysis, the risk of EC recurrence in patients with adenomyosis seemed to be irrelevant. Finally, in the case of overall survival, a multivariate analysis was not performed [ 56 ].…”
Section: Clinical Studiesmentioning
confidence: 99%